Nano Cs0. 32WO3 catalyst as well as preparation method and application thereof

By preparing nano Cs0.32WO3 catalyst with piezoelectric properties under dark conditions, using citric acid oxidation and complexation to form oxygen vacancy and W5+/W6+, the problem of ineffectiveness of Cs0.32WO3 catalyst in the prior art is solved in the prior art. , achieving efficient degradation and stability improvement of organic matter.

CN119114054AActive Publication Date: 2024-12-13SHAANXI UNIV OF SCI & TECH

Patent Information

Application Number
CN202411335051.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-13
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The existing Cs0.32WO3 catalyst cannot catalyze the catalytic degradation of organic pollutants under dark conditions, which is limited by light, resulting in low organic pollutant removal efficiency.

Method used

NanoCs0.32WO3 catalyst is prepared by heating and stirring tungsten chloride and cesium nitrate in ethanol, mixing with citric acid solution, and solvothermal reaction to form a hexagonal phase crystal with piezoelectric properties, which can be released by mechanical stress under dark conditions under conditions Catalytic degradation of electrons and holes.

Benefits of technology

It realizes efficient broad-spectrum cyclic degradation of organic matter under dark conditions, improves the degradation ability and stability of the catalyst, has piezoelectric characteristics, and can perform efficient degradation under simulated sunlight and near-infrared light.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a nano Cs0. 32WO3 catalyst and a preparation method and application thereof.The preparation method comprises the following steps that 1, tungsten chloride powder and cesium nitrate powder are dispersed into ethyl alcohol, and a mixed solution is obtained; 2, heating and stirring the mixed solution, and mixing the mixed solution with a citric acid solution to obtain a reaction precursor solution; and step 3, carrying out solvothermal reaction on the reaction precursor solution at 180-240 DEG C, and washing and drying a product in the reaction solution after the reaction is finished, so as to obtain the Cs0. 32WO3 powder. The nano Cs0. 322WO3 catalyst has an efficient broad-spectrum cyclic degradation and mineralization effect on organic matters under a dark condition, and the catalytic degradation and mineralization capability of the nano Cs0. 322WO3 catalyst on the organic matters under simulated sunlight and near infrared rays through the photothermal effect is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of piezoelectric catalytic material preparation, and is specifically a nano Cs 0.32 WO3 catalyst and its preparation method and application. Background Art

[0002] The rapid development of industry has led to an increase in human demand for energy and serious damage to the natural environment. Environmental pollution is a major challenge facing mankind. Photocatalytic technology using semiconductor materials as catalysts has shown great advantages in controlling environmental pollution and efficiently utilizing solar energy.

[0003] Cesium tungsten bronze (Cs 0.32 WO3) exhibits good near-infrared (780-2500nm) absorption and plasma resonance (LSPR) photothermal effect due to its unique local surface. 0.32 WO3 has good chemical stability, is easy to synthesize, is environmentally friendly, and has good particle size controllability, especially Cs 0.32 The hexagonal morphology of WO3 nanocrystals shows good performance in near-infrared light absorption. At present, pure phase cesium tungsten bronze is mostly used for near-infrared shielding and degradation of organic pollutants in water under visible light. Patents CN115924973A and CN115138354B use WCl6 and CsNO3 as raw materials and acetic acid as mineralizer to solvothermally prepare nano-granular Cs 0.32 WO3 crystal. Although it can degrade tetracycline hydrochloride under visible light and near-infrared light, it has no degradation ability under dark conditions. The literature (Applied Catalysis B: Environmental 183 (2016) 142–148) reported that WCl6 was dissolved in dehydrated ethanol and stirred vigorously, CsOH·H2O was added, and acetic acid was added after the mixture was uniform. Mixed valence Cs 0.32 WO3 nanorods. Cs 0.32 WO3 crystal contains W 5+ / W 6+ , excited by visible light and near-infrared light (>500 nm), a small polaron transition effect is produced, in which some escaped electrons go to the adjacent W position, thus forming a new W 5+ The remaining escaped electrons are captured by dissolved oxygen O2 in the solution to form ·O2 − , and then form ·OH, ·OOH and 1 O2,W 6 + Site and OH − React again and return W5+ The active components are OH and 1 O2 has sufficient energy for the redox reaction of organic pollutants. 0.32 WO3 nanorods can degrade methylene blue in the full spectrum of ultraviolet, visible light and near infrared. That is, the published patents and literature all use acetic acid as a mineralizer to solvothermally prepare Cs 0.32 WO3 crystal or Cs 0.32 WO3 nanorods, Cs 0.32 WO3 crystal contains W 5+ / W 6+ , resulting in a small polaron transition effect. Due to the complexation of acetic acid, oxygen vacancies and W cannot be generated simultaneously. 5+ / W 6+ , the generated Cs 0.32 WO3 nanorods have no piezoelectric properties, Cs 0.32 WO3 crystals can degrade organic pollutants only in the ultraviolet, visible and near-infrared full spectrum regions, and have no piezoelectric properties or the ability to degrade organic pollutants piezoelectrically in the dark.

[0004] However, the application of photocatalytic technology is limited due to the diffuse and regional characteristics of sunlight, and the existing Cs 0.32 WO3 cannot catalyze the degradation of organic pollutants in the dark, resulting in the removal of organic pollutants being limited by light. Summary of the invention

[0005] In view of the problems existing in the prior art, the present invention provides a nano Cs 0.32 WO3 catalyst and its preparation method and application, the nano Cs 0.32 WO3 catalyst has a high-efficiency broad-spectrum cyclic degradation and mineralization effect on organic matter under dark conditions, and nano-Cs 0.32 The photothermal effect of WO3 catalyst improves the catalytic degradation and mineralization capacity of organic matter.

[0006] The present invention is achieved through the following technical solutions: A nano-Cs 0.32 The preparation method of WO3 catalyst comprises the following steps: Step 1, dispersing tungsten chloride powder and cesium nitrate powder in ethanol to obtain a mixed solution; Step 2, heating and stirring the mixed solution, and mixing it with the citric acid solution to obtain a reaction precursor solution; Step 3, the reaction precursor solution is subjected to a solvent thermal reaction at 180-240°C, and after the reaction is completed, the product in the reaction solution is washed and dried to obtain Cs 0.32 WO3 powder.

[0007] Preferably, in step 1, the molar ratio of tungsten chloride to cesium nitrate is 1:(0.505-0.525).

[0008] Preferably, in step 2, the heating temperature is 45-55° C. and the stirring time is 180-300 min.

[0009] Preferably, the molar ratio of tungsten chloride to citric acid is (1.12-1.14): (2.40-7.20).

[0010] Preferably, in step 3, the reaction time is 8 h to 20 h.

[0011] Preferably, in step 3, washing is specifically performed by first centrifugation washing with deionized water and then washing with anhydrous ethanol.

[0012] Preferably, in step 3, drying is specifically performed by vacuum drying at 75-85°C.

[0013] The present invention provides a nano Cs prepared by the above-mentioned preparation method. 0.32 WO3 catalyst, the nano-Cs 0.32 WO3 catalyst is hexagonal, with a space group of P63 / mcm(193), storing electrons and holes. 0.32 WO3 catalyst has piezoelectric properties.

[0014] The present invention provides the nano Cs 0.32 Application of WO3 catalyst for piezoelectric catalytic degradation of organic matter under dark conditions.

[0015] The present invention also provides the nano Cs 0.32 Application of WO3 catalyst in piezoelectric-photothermal catalytic degradation of organic matter under sunlight or near-infrared light.

[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention prepares non-stoichiometric nano-Cs with piezoelectric response by a one-step solvothermal method. 0.32 WO3 catalyst, so that there are oxygen vacancies and W in the crystal 5+ / W 6+ , resulting in the existence of a piezoelectric polarization field in the crystal, storing electrons and holes. When CsNO3 and WCl6 are dissolved in anhydrous ethanol solution and citric acid aqueous solution is added, oxidation and complexation reactions are formed. , further polymerized to form In the solvothermal reaction, The induction of long polymer chains resulted in the crystallization of long rod-shaped Cs 0.32 WO3 and fine particles of Cs 0.32 WO3, Cs with long rod-like structure 0.32WO3 dissolves and crystallizes along the (200) plane to form rod-shaped Cs 0.32 WO3, as time goes by, Cs 0.32 WO3 rod-shaped Cs 0.32 WO3 gradually dissolves and disappears, and crystallizes to form large particles of Cs 0.32 WO3 and rod-shaped Cs 0.32 WO3 coexistence structure. 0.32 Non-stoichiometric Cs in WO3 crystal structure + Existence makes Cs 0.32 Some W in WO3 crystal 6+ The W atoms have a large number of free carriers in the orbit, so they are reduced to a lower valence state, generating W 5+ , in Cs 0.32 WO3 crystal W 5+ There is a negative charge center around it, which binds a hole in W 5+ Around, in Cs 0.32 The top of the valence band in the WO3 crystal band gap forms an acceptor energy level, while the Cs 0.32 When WO3 crystal is formed, oxygen vacancies are formed in the crystal, and the excess electrons formed by oxygen vacancies are 0.32 Donors are formed at the bottom of WO3 crystal, resulting in Cs 0.32 WO3 has both electrons and holes, making Cs 0.32 The WO3 crystal lattice displacement generates a piezoelectric polarization electric field. Under dark conditions, mechanical stress perturbation is applied to the nano-Cs 0.32 The strain of WO3 catalyst produces an enhanced positive piezoelectric effect. Under the action of the enhanced piezoelectric polarization field under dark conditions, the stored electrons-holes are quickly released and piezoelectric charges are formed for efficient catalytic reaction. It has efficient degradation ability for organic matter under dark conditions. Under the illumination of simulated sunlight and near-infrared light, the enhanced piezoelectric polarization field, the bound stored e - and h + The LSPR effect forms Cs 0.32 Under the synergistic effect of the thermal expansion of the WO3 lattice, a piezoelectric high-energy thermal - 、High energy heat + and photogenerated O2 - , OH and piezoelectric charge e - and piezoelectric charge h + Free radicals such as chlorinated hydrocarbons degrade and mineralize organic pollutants.

[0017] The nano Cs 0.32 WO3 catalyst has high degradation efficiency for organic compounds such as bisphenol A under dark conditions and in the full spectrum range, and has good cyclic degradation stability.0.32 WO3 catalyst has good application prospects in the method of purifying water pollution under dark conditions and in the full spectrum range. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions in the examples of the present invention or the prior art, the drawings required for use in the examples or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are some examples of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0019] Figure 1 1 is the XRD diagram of the catalyst prepared in Examples 1 to 4 of the present invention.

[0020] Figure 2 It is the Raman graph of the catalyst prepared in Examples 1 to 4 of the present invention.

[0021] Figure 3 This is a TEM image of the catalyst prepared in Example 3 of the present invention.

[0022] Figure 4 This is a TEM image of the catalyst prepared in Example 4 of the present invention.

[0023] Figure 5 This is the absorbance curve of the catalyst prepared in Example 3 of the present invention to 70 mg / L methylene blue under dark conditions.

[0024] Figure 6 The EPR-TEMPO-h prepared in Example 3 of the present invention + picture Figure 7 It is a PFM phase and amplitude change diagram of the catalyst prepared in Example 1 of the present invention.

[0025] Figure 8 It is a PFM phase and amplitude change diagram of the catalyst prepared in Example 3 of the present invention.

[0026] Fig. 9 It is a PFM phase and amplitude change diagram of the catalyst prepared in Example 4 of the present invention.

[0027] Fig.10 The degradation performance of the catalysts prepared in Comparative Example 1 and Examples 1 to 4 of the present invention on 20 mg / L bisphenol A under dark conditions is shown.

[0028] Fig.11 It is the mass spectrum of the catalyst prepared in Example 3 of the present invention degrading 20 mg / L bisphenol A for 1 min under dark conditions and the charge-to-mass ratios at different peak positions.

[0029] Fig.12 The mass spectrum and charge-to-mass ratios of different peak positions of the catalyst prepared in Example 3 of the present invention for the degradation of 20 mg / L bisphenol A for 6 min under dark conditions.

[0030] Fig.13 It is the removal rate of 20 mg / L bisphenol ATOC by the catalyst prepared in Example 3 of the present invention.

[0031] Fig.14 This is a degradation diagram of the catalyst prepared in Example 3 of the present invention for cyclic degradation of 20 mg / L bisphenol A under dark conditions and 10 cycles.

[0032] Fig.15 The degradation performance of the catalysts prepared in Comparative Example 1 and Examples 1 to 4 of the present invention for 20 mg / L bisphenol A under simulated sunlight is shown.

[0033] Fig.16 The temperature changes of the bisphenol A aqueous solution system (a, b) and the Example 3+bisphenol A aqueous solution system (c, d) in the degradation reaction of 20 mg / L bisphenol A by the catalyst prepared in Example 3 of the present invention under simulated sunlight.

[0034] Fig.17 The degradation performance of the catalysts prepared in Comparative Example 1 and Examples 1 to 4 of the present invention for 20 mg / L bisphenol A under near infrared light.

[0035] Fig.18 The temperature changes of the bisphenol A aqueous solution system (a, b) and the Example 3+bisphenol A aqueous solution system (c, d) in the degradation reaction of 20 mg / L bisphenol A by the catalyst prepared in Example 3 of the present invention under near-infrared light. DETAILED DESCRIPTION

[0036] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0037] It should be noted that the process equipment or devices not specifically specified in the following examples are all conventional equipment or devices in the art.

[0038] It should be noted that the terms "include" and "have" and any variations thereof are intended to cover non-exclusive inclusions. For example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to define the scope of the present invention. Changes or adjustments in their relative relationships should also be regarded as the scope of the present invention without substantially changing the technical content.

[0039] The nano Cs 0.32 The preparation method of WO3 catalyst comprises the following steps: Step 1, dispersing tungsten chloride powder and cesium nitrate powder in ethanol to obtain a mixed solution; Step 2, heating and stirring the mixed solution, and mixing the citric acid solution to obtain a reaction precursor solution; Step 3, the reaction precursor solution is subjected to a solvent thermal reaction at 180-240°C for 8-20 hours, and after the reaction is completed, the product in the reaction solution is washed and dried to obtain Cs 0.32 WO3 powder.

[0040] In the mixed solution obtained in step 1 of the present invention, the molar ratio of W:Cs is 1:(0.505-0.525); the molar ratio of tungsten chloride to citric acid is (1.12-1.14):(2.40-7.20).

[0041] In step 2 of the present invention, the heating temperature is 45-55° C. and the stirring time is 180-300 min.

[0042] In step 3 of the present invention, washing is performed multiple times with deionized water and anhydrous ethanol respectively, and the filter cake after washing the precipitate is dried at 65° C. to 75° C. for 12 h.

[0043] The nano Cs obtained by the present invention 0.32 The WO3 catalyst has a hexagonal structure and a space group of P63 / mcm(193). Due to the oxidation and complexation of citric acid, the solvent thermal solution crystallization formed a catalyst containing oxygen vacancies and W 5+ / W 6+ Granular Cs 0.32 WO3 and rod-shaped Cs 0.32The coexistence structure of WO3 leads to the existence of piezoelectric polarization field in the crystal, which stores electrons and holes. The stored electrons-holes and the released piezoelectric charges under mechanical stress stirring in dark conditions have a good degradation effect on organic substances such as bisphenol A, and have good broad-spectrum cycle stability under dark conditions. Under simulated sunlight and near-infrared light, the enhanced piezoelectric polarization field and bound stored e - and h + The double plasma resonance (LSPR) effect, under the synergistic effect of the LSPR effect and the thermal effect, degrades and mineralizes organic pollutants.

[0044] Comparative Example 1 Step 1, disperse 1.1222 mmol WCl6 powder and 0.5669 mmol CsNO3 powder into 54 ml anhydrous ethanol solution to obtain a yellow solution; Step 2, the yellow solution was heated and stirred at 50°C for 240 min, and mixed with 20 mL of 0.36 mol / L acetic acid solution to obtain a purple turbid precursor solution; Step 3: The purple turbid precursor solution is subjected to a solvothermal reaction at 240°C for 20 hours. After the reaction is completed, the product in the reaction solution is washed, separated and dried to obtain a blue Cs 0.32 WO3 powder. The washing is performed multiple times with deionized water and anhydrous ethanol, and the filter cake after the precipitate is washed is dried at 80°C for 4 hours.

[0045] Example 1 Step 1, disperse 1.1222 mmol WCl6 powder and 0.5669 mmol CsNO3 powder into 54 ml anhydrous ethanol solution to obtain a yellow turbid solution; Step 2, the yellow turbid liquid was heated and stirred at 50° C. for 240 min, and mixed with 20 mL of 0.36 mol / L citric acid solution to obtain a purple turbid precursor solution; Step 3: Solvothermally react the purple turbid precursor solution at 200 °C for 8 h. After the reaction is completed, the product in the reaction solution is washed, separated and dried to obtain blue Cs 0.32 WO3 powder. The washing was performed with deionized water and anhydrous ethanol for multiple times, and the filter cake after the precipitate was washed was dried at 70°C for 12 h.

[0046] Example 2 Step 1, disperse 1.1222 mmol WCl6 powder and 0.5669 mmol CsNO3 powder into 54 ml anhydrous ethanol solution to obtain a yellow turbid solution; Step 2, the yellow turbid liquid was heated and stirred at 50° C. for 240 min, and mixed with 20 mL of 0.36 mol / L citric acid solution to obtain a purple turbid precursor solution; Step 3: The purple turbid precursor solution was subjected to a solvothermal reaction at 200 °C for 12 h. After the reaction was completed, the product in the reaction solution was washed, separated and dried to obtain a blue Cs 0.32 WO3 powder. The washing was performed with deionized water and anhydrous ethanol for multiple times, and the filter cake after the precipitate was washed was dried at 70°C for 12 h.

[0047] Example 3 Step 1, disperse 1.1222 mmol WCl6 powder and 0.5669 mmol CsNO3 powder into 54 ml anhydrous ethanol solution to obtain a yellow turbid solution; Step 2, the yellow turbid liquid was heated and stirred at 50° C. for 240 min, and mixed with 20 mL of 0.36 mol / L citric acid solution to obtain a purple turbid precursor solution; Step 3: The purple turbid precursor solution was subjected to a solvothermal reaction at 200 °C for 16 h. After the reaction was completed, the product in the reaction solution was washed, separated and dried to obtain a blue Cs 0.32 WO3 powder. The washing was performed with deionized water and anhydrous ethanol for multiple times, and the filter cake after the precipitate was washed was dried at 70°C for 12 h.

[0048] Example 4 Step 1, disperse 1.1222 mmol WCl6 powder and 0.5669 mmol CsNO3 powder into 54 ml anhydrous ethanol solution to obtain a yellow turbid solution; Step 2, the yellow turbid liquid was heated and stirred at 50° C. for 240 min, and mixed with 20 mL of 0.36 mol / L citric acid solution to obtain a purple turbid precursor solution; Step 3: The purple turbid precursor solution was subjected to a solvothermal reaction at 200 °C for 20 h. After the reaction was completed, the product in the reaction solution was washed, separated and dried to obtain a blue Cs 0.32 WO3 powder. The washing was performed with deionized water and anhydrous ethanol for multiple times, and the filter cake after the precipitate was washed was dried at 70°C for 12 h.

[0049] Example 5 Step 1, disperse 1.1222 mmol WCl6 powder and 0.5723 mmol CsNO3 powder into 54 ml anhydrous ethanol solution to obtain a yellow turbid solution; Step 2, the yellow turbid liquid was heated and stirred at 50° C. for 240 min, and mixed with 20 mL of 0.36 mol / L citric acid solution to obtain a purple turbid precursor solution; Step 3: The purple turbid precursor solution was subjected to a solvothermal reaction at 200 °C for 16 h. After the reaction was completed, the product in the reaction solution was washed, separated and dried to obtain a blue Cs 0.32 WO3 powder. The washing was performed with deionized water and anhydrous ethanol for multiple times, and the filter cake after the precipitate was washed was dried at 70°C for 12 h.

[0050] Example 6 Step 1, disperse 1.1222 mmol WCl6 powder and 0.5779 mmol CsNO3 powder into 54 ml anhydrous ethanol solution to obtain a yellow turbid solution; Step 2, the yellow turbid liquid was heated and stirred at 50° C. for 240 min, and mixed with 20 mL of 0.36 mol / L citric acid solution to obtain a purple turbid precursor solution; Step 3: The purple turbid precursor solution was subjected to a solvothermal reaction at 200 °C for 16 h. After the reaction was completed, the product in the reaction solution was washed, separated and dried to obtain a blue Cs 0.32 WO3 powder. The washing was performed with deionized water and anhydrous ethanol for multiple times, and the filter cake after the precipitate was washed was dried at 70°C for 12 h.

[0051] Example 7 Step 1, disperse 1.1222 mmol WCl6 powder and 0.5835 mmol CsNO3 powder into 54 ml anhydrous ethanol solution to obtain a yellow turbid solution; Step 2, the yellow turbid liquid was heated and stirred at 50° C. for 240 min, and mixed with 20 mL of 0.36 mol / L citric acid solution to obtain a purple turbid precursor solution; Step 3: The purple turbid precursor solution was subjected to a solvothermal reaction at 200 °C for 16 h. After the reaction was completed, the product in the reaction solution was washed, separated and dried to obtain a blue Cs 0.32 WO3 powder. The washing was performed with deionized water and anhydrous ethanol for multiple times, and the filter cake after the precipitate was washed was dried at 70°C for 12 h.

[0052] Example 8 Step 1, disperse 1.1429mmol WCl6 powder and 0.5989mmol CsNO3 powder into 54ml anhydrous ethanol solution to obtain a yellow turbid liquid; Step 2, the yellow turbid liquid was heated and stirred at 50° C. for 240 min, and mixed with 20 mL of 0.36 mol / L citric acid solution to obtain a purple turbid precursor solution; Step 3: The purple turbid precursor solution was subjected to a solvothermal reaction at 200 °C for 16 h. After the reaction was completed, the product in the reaction solution was washed, separated and dried to obtain a blue Cs 0.32 WO3 powder. The washing was performed with deionized water and anhydrous ethanol for multiple times, and the filter cake after the precipitate was washed was dried at 70°C for 12 h.

[0053] Example 9 Step 1, disperse 1.1222 mmol WCl6 powder and 0.5669 mmol CsNO3 powder into 54 ml anhydrous ethanol solution to obtain a yellow turbid solution; Step 2, the yellow turbid liquid was heated and stirred at 50° C. for 240 min, and mixed with 20 mL of 0.36 mol / L citric acid solution to obtain a purple turbid precursor solution; Step 3: The purple turbid precursor solution was subjected to solvothermal reaction at 180°C for 16 h. After the reaction was completed, the product in the reaction solution was washed, separated and dried to obtain blue Cs 0.32 WO3 powder. The washing was performed with deionized water and anhydrous ethanol for multiple times, and the filter cake after the precipitate was washed was dried at 70°C for 12 h.

[0054] Example 10 Step 1, disperse 1.1222 mmol WCl6 powder and 0.5669 mmol CsNO3 powder into 54 ml anhydrous ethanol solution to obtain a yellow turbid solution; Step 2, the yellow turbid liquid was heated and stirred at 50° C. for 240 min, and mixed with 20 mL of 0.36 mol / L citric acid solution to obtain a purple turbid precursor solution; Step 3: The purple turbid precursor solution was subjected to solvothermal reaction at 190 °C for 16 h. After the reaction was completed, the product in the reaction solution was washed, separated and dried to obtain blue Cs 0.32 WO3 powder. The washing was performed with deionized water and anhydrous ethanol for multiple times, and the filter cake after the precipitate was washed was dried at 70°C for 12 h.

[0055] Embodiment 11 Step 1, disperse 1.1222 mmol WCl6 powder and 0.5669 mmol CsNO3 powder into 54 ml anhydrous ethanol solution to obtain a yellow turbid solution; Step 2, the yellow turbid liquid was heated and stirred at 50° C. for 240 min, and mixed with 20 mL of 0.36 mol / L citric acid solution to obtain a purple turbid precursor solution; Step 3: The purple turbid precursor solution was subjected to a solvothermal reaction at 220°C for 16 h. After the reaction was completed, the product in the reaction solution was washed, separated and dried to obtain a blue Cs 0.32 WO3 powder. The washing was performed with deionized water and anhydrous ethanol for multiple times, and the filter cake after the precipitate was washed was dried at 70°C for 12 h.

[0056] Example 12 Step 1, disperse 1.1222 mmol WCl6 powder and 0.5669 mmol CsNO3 powder into 54 ml anhydrous ethanol solution to obtain a yellow turbid solution; Step 2, the yellow turbid liquid was heated and stirred at 50° C. for 240 min, and mixed with 20 mL of 0.36 mol / L citric acid solution to obtain a purple turbid precursor solution; Step 3: The purple turbid precursor solution was subjected to solvothermal reaction at 240 °C for 16 h. After the reaction was completed, the product in the reaction solution was washed, separated and dried to obtain blue Cs 0.32 WO3 powder. The washing was performed with deionized water and anhydrous ethanol for multiple times, and the filter cake after the precipitate was washed was dried at 70°C for 12 h.

[0057] Example 13 Step 1, disperse 1.1222 mmol WCl6 powder and 0.5669 mmol CsNO3 powder into 54 ml anhydrous ethanol solution to obtain a yellow turbid solution; Step 2, the yellow turbid liquid was heated and stirred at 50° C. for 240 min, and mixed with 20 mL of 0.12 mol / L citric acid solution to obtain a purple turbid precursor solution; Step 3: The purple turbid precursor solution was subjected to a solvothermal reaction at 200 °C for 16 h. After the reaction was completed, the product in the reaction solution was washed, separated and dried to obtain a blue Cs 0.32 WO3 powder. The washing was performed with deionized water and anhydrous ethanol for multiple times, and the filter cake after the precipitate was washed was dried at 70°C for 12 h.

[0058] Embodiment 14 Step 1, disperse 1.1222 mmol WCl6 powder and 0.5669 mmol CsNO3 powder into 54 ml anhydrous ethanol solution to obtain a yellow turbid solution; Step 2, the yellow turbid liquid was heated and stirred at 50°C for 240 min, and mixed with 20 mL of 0.20 mol / L citric acid solution to obtain a purple turbid precursor solution; Step 3: The purple turbid precursor solution was subjected to a solvothermal reaction at 200 °C for 16 h. After the reaction was completed, the product in the reaction solution was washed, separated and dried to obtain a blue Cs 0.32 WO3 powder. The washing was performed with deionized water and anhydrous ethanol for multiple times, and the filter cake after the precipitate was washed was dried at 70°C for 12 h.

[0059] Embodiment 15 Step 1, disperse 1.1222 mmol WCl6 powder and 0.5669 mmol CsNO3 powder into 54 ml anhydrous ethanol solution to obtain a yellow turbid solution; Step 2, the yellow turbid liquid was heated and stirred at 50° C. for 240 min, and mixed with 20 mL of 0.24 mol / L citric acid solution to obtain a purple turbid precursor solution; Step 3: The purple turbid precursor solution was subjected to a solvothermal reaction at 200 °C for 16 h. After the reaction was completed, the product in the reaction solution was washed, separated and dried to obtain a blue Cs 0.32 WO3 powder. The washing was performed with deionized water and anhydrous ethanol for multiple times, and the filter cake after the precipitate was washed was dried at 70°C for 12 h.

[0060] The above conclusions and mechanisms are explained in detail below.

[0061] Figure 1 The XRD diagram of the catalyst prepared in Examples 1 to 4 of the present invention. 0.32 The diffraction peaks of WO3 powder at 13.8°, 23.4°, 27.2°, 27.7°, 33.8° and 36.6° correspond to Cs 0.32 The (100), (002), (102), (200), (112) and (202) crystal planes of WO3 are similar to those of hexagonal Cs 0.32 The standard card of WO3 (JCPDS: 83-1334) is consistent, belonging to the hexagonal phase of space group: P63 / mcm (193), indicating that the present invention successfully prepared hexagonal nano-Cs by solvothermal reaction. 0.32 WO3 crystal.

[0062] Figure 2 is the Raman graph of the catalysts prepared in Examples 1 to 4 of the present invention. It can be seen that the catalysts in Examples 1 to 4 have a high -1 and 300 cm -1 There is a stretching vibration peak of the WO bond at 440 cm-1 The W=O bond stretching vibration peak of Example 3 is the strongest, indicating that it has more W=O bonds. 5+ =O bond. Raman graph further proves that the hexagonal Cs 0.32 WO3.

[0063] Figure 3 and Figure 4 Cs 0.32 TEM image of WO3 crystal, Figure 3 The catalyst of Example 3 is composed of a rod-like structure with a diameter of about 10-50 nm and a length of 50-200 nm and particles of 5-10 nm, and Figure 4 The catalyst of Example 4 is composed of rod-like structures with a diameter of about 10 nm and a length of 100 nm and particles with a diameter of 5-10 nm.

[0064] Figure 5 is Cs prepared in Example 3 of the present invention 0.32 The absorbance curve of WO3 catalyst to 70 mg / L methylene blue under dark conditions. The nano-Cs 0.32 The electron concentration stored in WO3 is 315.15 μmol·g -1 Therefore, the prepared nano-Cs 0.32 WO3 is an energy storage catalyst.

[0065] Figure 6 is Cs prepared in Example 3 of the present invention 0.32 TEPO-h under dark conditions with WO3 catalyst + Characteristic signal spectrum, Cs is calculated from the quantum spin number (L) 0.32 WO3 h + The storage concentration is 209.07 µmol / g.

[0066] Figure 7 , Figure 8 and Fig. 9 Cs prepared in Examples 1, 3 and 4 of the present invention 0.32 Phase change diagram of WO3 catalyst. Nano-Cs 0.32 After applying a 10 V deflection voltage, the phase angle of WO3 flipped by about 180°, proving that the dipole is easily transformed by an external electric field. The piezoelectric coefficients (d 33 ) are 8.99 nm / V, 9.29 nm / V and 5.82 nm / V respectively, showing good piezoelectric performance. The larger piezoelectric polarization characteristics can induce the catalyst to store charge and generate piezoelectric charge under mechanical stress, thus improving the catalytic activity under dark conditions.

[0067] Fig.10 The degradation performance of the catalysts prepared in Comparative Example 1 and Examples 1 to 4 of the present invention on 20 mg / L bisphenol A. Under dark conditions, the degradation rates of the catalysts prepared in Comparative Example 1 and Examples 1 to 4 on 20 mg / L BPA in 6 min were 67.59%, 65.83%, 72.04%, 72.78% and 71.62%, respectively. Although the degradation rate of Comparative Example 1 in 6 min was higher than that of Example 1, the degradation rate of Example 1 in 0 to 1 min was 57.97%, and the degradation rate of Comparative Example 1 in 0 to 1 min was 44.04%, indicating that due to the oxidation and complexation of citric acid, Example 1 induced crystallization to form a long rod-shaped structure of Cs 0.32 WO3 crystal, the electron-hole concentration stored in Example 1 is higher than that in Comparative Example 1, but the long rod-shaped structure formed in Example 1 releases less piezoelectric charge than that in Comparative Example 1, resulting in a low degradation rate in 1-6 minutes. However, as time goes by, Cs 0.32 WO3 rod-shaped Cs 0.32 WO3 gradually dissolves and disappears, and crystallizes to form large particles of Cs 0.32 WO3 and rod-shaped Cs 0.32 WO3 coexistence structure. The degradation rates of Examples 2 to 4 are significantly greater than that of Comparative Example 1. Fig.11 and Fig.12 The following are the mass spectra of the catalyst prepared in Example 3 of the present invention degrading 20 mg / L bisphenol A for 1 min and 9 min under dark conditions. The LC-MS detection of bisphenol A from high mass-to-charge ratio (m / z=227) to small molecules further proves that nano-Cs 0.32 WO3 catalyst can degrade bisphenol A into CO2, H2O and small molecular organic matter under dark conditions, indicating that nano-Cs 0.32 The reaction of WO3 catalyst to bisphenol A under dark conditions is degradation and mineralization, not adsorption reaction.

[0068] Fig.13 The TOC removal rate of the catalyst prepared in Example 3 of the present invention for 20 mg / L bisphenol A degradation for 6 min was 22.50% under dark conditions, further proving that the Cs 0.32 WO3 crystals have a degradation and mineralization effect on bisphenol A.

[0069] Fig.14 The catalyst prepared in Example 3 of the present invention degraded 20 mg / L bisphenol A ten times under dark conditions. 0.32 WO3 crystals still have a degradation efficiency of 59.75% for BPA, indicating that the Cs 0.32 WO3 crystals have cyclic degradation stability to bisphenol A.

[0070] Fig.15 The degradation performance of the catalysts prepared in comparative example 1 and examples 1-4 of the present invention on 20 mg / L bisphenol A under simulated sunlight. Under simulated sunlight, the degradation rates of the catalysts prepared in comparative example 1 and examples 1-4 on 20 mg / L bisphenol A were 69.10%, 65.83%, 72.04%, 77.57% and 71.62% respectively in 90 min. The reason why the degradation rate of comparative example 1 is greater than that of example 1 is the same as that under dark conditions.

[0071] Fig.16 The temperature change of the catalyst prepared in Example 3 of the present invention in the degradation reaction system of 20 mg / L bisphenol A under simulated sunlight. The temperature of 20 mg / L bisphenol A aqueous solution at room temperature is 25.4°C ( Fig.16 a), after 90 minutes of simulated sunlight irradiation, the temperature was 43.8℃ ( Fig.16 b), after 90 minutes of simulated sunlight irradiation, the temperature of the 20 mg / L bisphenol A aqueous solution system changed by 43.8-25.4=18.4°C; the temperature of the 20 mg / L bisphenol A+ aqueous solution system of Example 3 at room temperature was 27.8°C ( Fig.16 c), after 90 minutes of simulated sunlight, the temperature was 58.3℃ ( Fig.16 d) After 90 minutes of simulated sunlight irradiation, the temperature of the 20 mg / L bisphenol A+ aqueous solution of Example 3 changes by 58.3-27.8=30.5°C. This indicates that under simulated sunlight, the temperature of the catalyst degradation reaction system of Example 3 rises by about 30.5-18.4=12.1°C, indicating that the nano-Cs prepared by the present invention 0.32 WO3 catalyst has photothermal effect under simulated sunlight.

[0072] Fig.17 The degradation performance of the catalysts prepared in Comparative Example 1 and Examples 1 to 4 of the present invention on 20 mg / L bisphenol A under near infrared light. Under near infrared light, the degradation rates of the catalysts prepared in Comparative Example 1 and Examples 1 to 4 on 20 mg / L bisphenol A were 63.61%, 68.91%, 72.03%, 73.10% and 69.93% respectively in 90 min. The electron hole concentration bound and stored in Example 1 is greater than that in Comparative Example 1. - and h + Under the synergistic effect of the double plasma resonance (LSPR) effect and the piezoelectric photothermal effect, the degradation rate of Example 1 is greater than that of Comparative Example 1.

[0073] Fig.18The temperature change of the catalyst prepared in Example 3 of the present invention in the degradation reaction system of 20 mg / L bisphenol A under near infrared light. The temperature of 20 mg / L bisphenol A aqueous solution at room temperature is 29.6°C ( Fig.18 a), temperature 46.4℃ after 90min of near-infrared light irradiation ( Fig.18 b), after 90 minutes of near-infrared light irradiation, the temperature of the 20 mg / L bisphenol A aqueous solution system changed by 46.4-29.6=16.8°C; the temperature of the 20 mg / L bisphenol A+ aqueous solution system of Example 3 was 28.3°C ( Fig.18 c), after 90 minutes of near-infrared light irradiation, the temperature was 54.9℃ ( Fig.18 d), the temperature of the aqueous solution of 20 mg / L bisphenol A + Example 3 changes by 54.9-28.3=26.6°C. This indicates that under near infrared light, the temperature of the catalyst degradation reaction system of Example 3 rises by about 26.6-16.8=9.8°C, indicating that the nano-Cs prepared by the present invention 0.32 WO3 catalyst has photothermal effect under near-infrared light.

[0074] The above is only one embodiment of the present invention, not all or the only embodiment. Any equivalent changes made to the technical solution of the present invention by ordinary technicians in this field after reading the specification of the present invention are covered by the claims of the present invention.

Claims

1. A nano-Cs 0.32 The method for preparing WO3 catalyst is characterized in that: The following steps are involved: Step 1, dispersing tungsten chloride powder and cesium nitrate powder in ethanol to obtain a mixed solution; Step 2, heating and stirring the mixed solution, and mixing it with the citric acid solution to obtain a reaction precursor solution; Step 3, the reaction precursor solution is subjected to a solvent thermal reaction at 180-240°C, and after the reaction is completed, the product in the reaction solution is washed and dried to obtain Cs 0.32 WO3 powder.

2. A nano Cs according to claim 1 0.32 The method for preparing WO3 catalyst is characterized in that: In step 1, the molar ratio of tungsten chloride to cesium nitrate is 1:(0.505-0.525).

3. A nano Cs according to claim 1 0.32 The preparation method of WO3 catalyst is characterized in that: In step 2, the heating temperature is 45-55°C and the stirring time is 180-300 min.

4. A nano Cs according to claim 1 0.32 The preparation method of WO3 catalyst is characterized in that: The molar ratio of tungsten chloride to citric acid is (1.12~1.14): (2.40~7.20).

5. A nano Cs according to claim 1 0.32 The preparation method of WO3 catalyst is characterized in that: In step 3, the reaction time is 8 h to 20 h.

6. A nano Cs according to claim 1 0.32 The method for preparing WO3 catalyst is characterized in that: In step 3, washing is specifically performed by first centrifugation washing with deionized water and then washing with anhydrous ethanol.

7. A nano Cs according to claim 1 0.32 The preparation method of WO3 catalyst is characterized in that: In step 3, drying is specifically performed by vacuum drying at 75-85°C.

8. A nano-Cs prepared by the preparation method according to any one of claims 1 to 7 0.32 WO3 catalyst, characterized in that The nano-Cs 0.32 WO3 catalyst is hexagonal, with a space group of P63 / mcm(193), storing electrons and holes. 0.32 WO3 catalyst has piezoelectric properties.

9. The nano Cs according to claim 8 0.32 Application of WO3 catalyst for piezoelectric catalytic degradation of organic matter under dark conditions.

10. The nano-Cs according to claim 8 0.32 Application of WO3 catalyst in piezoelectric-photothermal catalytic degradation of organic matter under sunlight or near-infrared light.

Citation Information

Patent Citations

  • Cesium tungsten bronze powder and preparation method thereof

    CN102320662A

  • Hexagonal crystal tungsten bronze short rod nanoparticles and preparation method thereof

    CN105502503A

  • nTi-MxWO3 composite nanoparticles with mesoporous structure and preparation method of composite nanoparticles

    CN110723753A

  • Cs0. 32WO3 / (m-t)-BiVO4 heterojunction as well as preparation method and application thereof

    CN115924973A

  • Method for producing tungsten complex oxide particles

    US20170190593A1

Cited By

  • Application of MxCs0.32-xWO3 piezoelectric crystal in catalytic degradation of organic pollutants

    CN120841654A